ANALISIS STRATEGI PEMASARAN UNTUK MENINGKATKAN PENJUALAN PADA PT BHIRAWA STEEL PASCA AKUISISI PT HUTAMA KARYA (PERSERO) - Devira Rachmadayanti, Levia; Harsono, Soni (JURNAL EKBIS, 2023)
This research was carried out with the aim of identifying the marketing strategies carried out by PT. Bhirawa Steel. This research's marketing strategy analysis uses SWOT analysis, using qualitative research design methods. Information related to marketing strategy was obtained from direct interviews with all informants, conducting field observations, and collecting secondary data on the company. The result of this research is that the implementation of marketing strategies at PT. Bhirawa Steel has been running well, even though it is not perfect. The most important thing in the successful implementation of this marketing strategy is the commitment of superiors and marketing managers to improve and control the competitive marketing strategy for steel products.